PCR screening of genetically modified maize in biscuit products using TNOS gene - George, Sabrina (2022)
Recently, Genetically Modified (GM) plants are employed extensively in a variety of commercial goods. The use of advanced methods of genetic engineering in agriculture has led to an increase in the production of genetically modified crops as well as food products. However, the use of complex molecular genetics technologies for their creation through nanobiotechnology manners to obtain genetically modified organisms, are not yet perfect, which causes a number of risks arising from the creation of such organisms. Maize is among the common genetically modified plants and has been integrated into the food and feed supply chains. In this study, the genetically modified TNOS gene was used to screen the biscuit samples bought from the market around Kota Bharu, Kelantan. DNeasy Mericon Food Kit was used to extract the biscuit samples, fresh maize, and GM maize positive control. PCR amplification was performed using zein and TNOS genes and results show all biscuit samples were absent of zein and TNOS genes. This could be caused by several reasons such as very low DNA concentration, the extracted DNA might be degraded, a different gene used for GM maize, the efficiency of conventional PCR and the sensitivity of agarose gel. Although the quantification reading for almost all samples showed an acceptable DNA concentration and good value for the first purity. Positive amplification for both genes was seen in the GM maize positive control.